Achieving Competitive Advantage Through The Role Of Training And Compensations Practices On Innovative Work Behavior: A Study In Jordan Islamic Banks - Esraa Farid Qawasmeh; Norailis Ab Wahab (Human Resource Management Academic Research Society, 2024)
Non-Indexed Publication